2011
DOI: 10.4028/www.scientific.net/amm.83.116
|View full text |Cite
|
Sign up to set email alerts
|

Formation of ZnO Nanorods via Seeded Growth Hydrothermal Reaction

Abstract: In this study, ZnO nanorods was formed on a seeded substrates prepared by thermal oxidation of Zn foil followed by hydrothermal reaction. ZnO seed was prepared via thermal oxidation process at 300°C for 10 minutes to form uniform circular nanosize grains that were suitable as a seeded template for the growth of ZnO nanorods via hydrothermal reaction. Several hydrothermal reaction parameters were studied; hydrothermal reaction temperature, ratio of zinc nitrate to hexamethylamine and pH. In hydrothermal reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Given that the ZnO growth rate is preferentially high at the c-axis, ZnO recrystallization causes growth on the [0001] plane. Thus, thinner and longer ZnO nanorods are produced with increased growth duration [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the ZnO growth rate is preferentially high at the c-axis, ZnO recrystallization causes growth on the [0001] plane. Thus, thinner and longer ZnO nanorods are produced with increased growth duration [5].…”
Section: Resultsmentioning
confidence: 99%
“…Seeded substrates are used in the hydrothermal technique to achieve well-controlled morphology and growth direction of ZnO nanorods. Heterogeneous nucleation favors the growth of ZnO nanorods because the interfacial energy between crystals and substrate is usually smaller than the interfacial energy between crystals and solution [5]. Therefore, pre-coating the substrate with seed materials similar to nanocrystals can effectively control nanorods growth and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the ZnO growth rate is preferentially high along the c-axis, that is why ZnO recrystallization causes growth on the [0 0 0 1] plane. Thus, thinner and longer ZnO nanorods are produced with increased growth duration [32]. (c) The core of flowerlike morphology was poorly crystallized and easily dissolves into ZnO aggregate during prolonged reaction time.…”
Section: Resultsmentioning
confidence: 99%
“…Sintesis nanopartikel ZnO sebagai fotokatalis dengan metode yang berbeda dapat menghasilkan karakteristik yang berbeda pula, beberapa metode yang dapat dilakukan diantaranya evaporasi termal, molecular beam epitaxy (MBE), deposisi elektrokimia, spray pyrolysis, dan metode sol-gel [11]. Metode sol-gel merupakan metode yang relatif sederhana, mudah, dan murah diantara metode lainnya [12].…”
Section: Pendahuluanunclassified
“…Sintesis nanopartikel ZnO sebagai fotokatalis dapat dilakukan dengan berbagai metode, namun proses sol-gel relatif lebih sederhana, biaya produksi rendah, dan dapat menghasilkan partikel berukuran nano pada suhu rendah [11,13]. Metode sol-gel terbagi menjadi enam tahapan, yakni proses hidrolisis dan kondensasi (sol terbentuk), kondensasi lanjutan (gel terbentuk), ageing process (endapan terbentuk), drying process (xerogel terbentuk), dan proses pembentukan xerogel menjadi fasa yang diinginkan [13].…”
Section: Metode Sol-gelunclassified